2015
DOI: 10.1016/j.avb.2015.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Sexualized war violence. Knowledge construction and knowledge gaps

Abstract: This qualitative literature review provides an overview of the proliferating research field that research on sexualized war violence has become. The article critically reviews some of the main theories on sexualized war violence in light of five basic and interrelated dimensions: terminology and conceptualizations, etiological approaches, disciplinary grounding, contextual emphasis, and, lastly, the policy implications these dimensions imply. The review involves a discussion of critical contestations within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The physical act of rape has dramatic consequences for victims. Researchers have found that the field of SGBV is overwhelmingly focused on female victims in part due to an overreliance on early feminist theory which helped to define the field of violence against women (Dobash, 1979; Houge, 2015; Walker, 1979). While women are often victims, our research found that not only are men impacted by SGBV, but they can experience direct and indirect victimization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical act of rape has dramatic consequences for victims. Researchers have found that the field of SGBV is overwhelmingly focused on female victims in part due to an overreliance on early feminist theory which helped to define the field of violence against women (Dobash, 1979; Houge, 2015; Walker, 1979). While women are often victims, our research found that not only are men impacted by SGBV, but they can experience direct and indirect victimization.…”
Section: Discussionmentioning
confidence: 99%
“…Examining SGBV as only a woman’s concern reinforces the hegemonic gender-binary view that SGBV does not include men (Dolan, 2014). Some researchers argue that male perpetrators should be studied in tandem with female victims, to better understand the mechanisms through which the decision to use SGBV against a woman occurs (Houge, 2015). Additionally, researchers have shown that men in the DRC are impacted by SGBV as victims of SGBV and family members of female victims of SGBV (Bjørkhaug & Bøås, 2014; Johnson et al, 2010).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviews of the contemporary knowledge base concerning the causes of conflict‐related sexual violence often highlight two prevailing “knowledge camps”: one that understands rape and sexual violence as sexual opportunism, and another that explains conflict‐related sexual violence as a weapon of war (Houge ; Meger ). According to Meger (: 150), scholars in the opportunism camp suggest that soldiers rape because war provides them with ample opportunity to do so, as if there is something inherent in either men qua men, or in the conditioning of men into soldiers, that make them rape unless it is prevented.…”
Section: Current Debatesmentioning
confidence: 99%
“…According to Meger (: 150), scholars in the opportunism camp suggest that soldiers rape because war provides them with ample opportunity to do so, as if there is something inherent in either men qua men, or in the conditioning of men into soldiers, that make them rape unless it is prevented. These approaches are best understood along a continuum and take in various degrees of inherent, situational, and/or societal or structural factors that condition and encourage soldiers to rape for the purpose of self‐gratification (Houge ). These understandings emphasize the opportunities created by the chaos of war, which suggest that “preventing conflict‐related sexual violence requires stricter enforcement policies, norms, and codes of conduct to curtail this behavior” (Meger ).…”
Section: Current Debatesmentioning
confidence: 99%